On the Impact of Self Assessment on EFL Learners' Receptive Skills Performance. - Shahrakipour, Hassan (International Research Journal of Art & Humanities, 2014)
It is believed that self assessment can influence learners' learning achievement (Dearing, 1997; Falchikov, 1997; Stefani, 1998; Taras, 2001, 2002). it can also influence language learners' writing and speaking performance ((Alibakhshi & Abbaszadeh, 2012).However, the impact of self assessment on EFL learners' listening and writing was not studied yet. This study was an attempt to see whether self assessment can influence EFL learners' receptive skills. It also tried to see whether it has the same effect on intermediate and beginner language learners. In doing so, 120 Iranian language learners were selected through convenience sampling and divided into beginner and intermediate language learners. The experimental groups received a treatment on self assessment and they self assessed their outcomes. All groups received a posttest. The data were analyzed through Acnova test. The results showed that self assessment significantly improved EFL learners' receptive skills. However, the effect value of self assessment for listening skill was less than reading skill. Also, self assessment effect value on beginner groups was less in comparison with intermediate groups.